Optimalisasi Produktivitas Kerja melalui Sistem Manajemen Kinerja: Peran Kepuasan Kerja sebagai Faktor Intervensi - Partimah, Partimah; Sutianingsih, Sutianingsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to examine the influence of performance management on work productivity through job satisfaction. The research population is 134 employees of the Grobogan Regency Regional Secretariat. Quantitative methods are used in this study. Using SPSS 26, a wide variety of tests are performed, including validity and reliability tests, hypothesis tests, multiple regression analysis tests, and Sobel tests. Management effectiveness and employee happiness have a positive and statistically significant influence on workplace output. This means that along with the increase in the level of performance management and job satisfaction, employee performance also increases. In the sobel test, it produces a positive and significant influence on performance management on work productivity through job satisfaction. Keywords: job management, job satisfaction, work productivity